PERBEDAAN HASIL BELAJAR ADMISTRASI UMUM MENGGUNAKAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING DENGAN ROLE PLAYING SISWA KELAS X SMK SWASTA AR-RAHMANMEDAN TAHUN PELAJARAN 2021-2022 - Ayu Putri Handayani; Zulkifli Hasibuan (Sekolah Tinggi Pariwisata Mataram, 2022)
The type of research used is quantitative research. The data collection instrument was a multiple choice test with 30 items. The sampling technique used is the saturated sampling technique. Where the entire total population is 60 people while the set sample is 20 people as the research sample. From the results of the study, it was obtained that the average learning outcomes using the learning model Student facilitator and explaining was 84.3 and role playing was 83.5. Based on the results of the calculation of the hypothesis test above, the results obtained are significant with a = 0.05 and dk = ( n1-2) = ( 27-2) = 25. Then it is obtained, the results of tcount = 2.51 and ttable = 1.69 are obtained from the t distribution list, with tcount > ttable, thus the hypothesis formulated in this study is that there are differences in student learning outcomes between learning using the student facilitator learning model and explaining to the students of class x private SMK Ar Rahman Medan. Its existence can be accepted because tcount > ttable, which means that the results of students using the Student Facilitator and Explaining learning model are higher than student learning outcomes using the Role Playing learning model in class x students of Ar Rahman Private Vocational School Medan. Learning year 2021/2022.